PENGGUNAAN MEDIA FLASH CARD DALAM MENGAJARKAN KOSA KATA BAHASA INGGRIS PADA ANAK SEKOLAH DASAR - RIRIS NUR KHOLIDAH (NIZHAMIYAH, 2017)
Giving the right stimulus in early stage of age gives a very great impact to the next human development process. There are many methods that we can apply for balancing the right brain and the left brain capability. One of them is using a flash card as a media which uses a card game. Flash card is an effective media to teach children in reading a text and knowing their surrounding in an early age. Trough flash card we can introduce colours, animals, letters, numbers, and other things. In principle, introducing the learning materials trough flash card can be delivered in a simple way and the most important is a pleasure atmosphere both for the children (the learner) and the teacher. Therefore, we can conclude that eventhough the learning process only takes a few minutes but it gives a big benefit for our children.